Hepatoprotective and Antioxidant Effect of Vitamin C and E Against Some Common Non-steroidal Antiinflammatory Drugs Induced Hepatic Damage in Rats - Darbar, Soumendra; Bose, Sandeep; Chatterjee, Nilendra; Roy, Bikash; Kumar Chattarajee, Tapas; Kumar Pal, Tapan (Asian Journal of Chemistry, 2010)
Non-steroidal antiinflammatory drugs (NSAIDs) are among the most frequently prescribed drugs worldwide. Hepatotoxicity is the most serious adverse effects of aceclofenac and diclofenac sodium. This study was designed to evaluate the hepatoprotective activity of vitamin C and E against NSAIDs induced acute liver injury in rats and to determine its mechanism of action. Administration of vitamin C and E (200 mg/kg/ d) as a food supplement for 28 d significantly reduced the elevated relative values of liver weight, serum transaminases (alanine aminotransferase and aspertate aminotransferase), alkaline phosphatase, blood urea nitrogen, bilirubin (total and direct), total cholesterol and the hepatic morphological changes induced by aceclofenac (120 mg/kg/d) and diclofenac (120 mg/kg/d) in rats. However, simultaneous treatment with vitamin C and E as a food supplement (200 mg/kg/d) significantly attenuated aceclofenac and diclofenac induced hepatotoxicity. Histopathological damage of liver and the number of apoptotic hepatocytes were also significantly ameliorated by vitamin C and E treatment. It is therefore, suggested that combination of vitamins C and E had significant hepatoprotective activity and its mechanism is related at least in part, to its antioxidant properties.